Current trends in private financing of public primary education in Congo Brazzaville - Okoua, Béatrice Perpétue (International Journal of Social Service and Research, 2023)
The study carried out on current trends in private financing of primary education in Congo Brazzaville has the main objective of verifying the financing capacity of the State and parents in the education of children in public primary school. To answer questions relating to free education and the difficulties that the Congolese experience in financing the education of children, we have retained as data collection instruments, the documentary study and the interview. We have selected a sample of five ( 05) schools per constituency chosen out of twenty five (25) and questioned two hundred (200) parents distributed by category according to their income. The results obtained confirm our initial hypotheses that the Congolese State is experiencing enormous difficulties in resuming the educational situation hand and free appears as a concept which does not evoke any reality with the parents, (80.5%) deny free, (19.5%) grant him a credit. The hypotheses formulated and validated allowed us to propose suggestions for solution approaches to the main education partners.